Application of RAPD in the study of genetic variations between African and American Cichlidae - Goldberg, D; Jackson, K; Yehuda, Y; Plotzky, Y; Degani, G (Indian Journal of Fisheries, 2011)
The DNA of a number of species of the family Cichlidae, found in Africa (Malawi Lake) and in North America (Mexico), was compared by random amplified polymorphic DNA (RAPD). The species examined in this study were : Hemichromis bimaculatus (American cichlid), Pseudotropheus zebra (red dorsal), Cyanotilapia afra mbamba (red top), Labidochromis flavigulus and Pseudotropheus tropheus (red cheek). Nine primers were examined in PCR reaction, of which three were found suitable for use in this technique (ZG4, ZG8 and 118). Band sharing (BS) within each species with these primers was : 0.00-0.29 in H. bimaculatus, 0.40- 1.00 in L. flavigulus, 0.00-0.25 in P. tropheus, 0.00-1.00 in C. afra and 0.00-0.25 in P. zebra. With all the primers the lowest genetic variation (common bands : 4-8; BS : 0.85-1.00) was found between P. zebra and P. tropheus. A high genetic variation (common bands : 0-4; BS : 0-0.06) was found between American Cichlidae (H. bimaculatus) and all the other species (African Cichlidae). The advantage of this method for measuring variability between species (including hybrids) of the Cichlidae is discussed.